Effect of operating temperature on direct recycling aluminium chips (AA6061) in hot press forging process - Yusuf, Nur Kamilah; Lajis, Mohd Amri; Daud, M.I.; Noh, Mohamad Zaky (Trans Tech Publications, 2014)
A method of solid-state recycling aluminum alloy using hot press forging process was studied as well as the possibility of the recycled chip to be used as secondary resources. This paper presents the results of recycled AA6061 aluminium alloy chip using different operating temperature for hot press forging process. Mechanical properties and microstructure of the recycled specimens and as-received (reference) specimen were investigated. The recycled specimens exhibit a good potential in the strength properties. The result for yield strength (YS) and ultimate tensile strength (UTS) at the minimum temperature 430˚C is 25.8 MPa and 27.13 MPa. For the maximum operating temperature 520˚C YS and UTS are 107.0MPa and 117.53 MPa. Analysis for different operating temperatures shows that the higher temperatures giving better result on mechanical properties and finer microstructure. The strength of recycled specimen increases due to the grain refinement strengthening whereas particle dispersion strengthening has minor effects. In this study, the recycled AA6061 chip shows the good potential in strengthening as the comparison of using only 17.5% of suggested pressure (70.0/400.0) MPa, the UTS exhibit 35.8% (117.58/327.69) MPa. This shows a remarkable potential of direct recycling by using hot press forging process.